Peran Pendidikan Keperawatan Menghadapi Era Society 5.0 - Agnes Mahayanti; Ismoyo Ismoyo (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2021)
The world progress of education goes hand in hand with the development of the era of society 5.0. The purpose of this paper is to describe the role of nursing education in adapting the demands of the era of society 5.0 so that it can answer the challenge of improving students' critical, constructive and innovative thinking skills. The method used is a literature review using various references derived from the results of research or the thoughts of other authors. Currently, the Indonesian people have just been faced with the issue of the industrial revolution 4.0, but now they have to adapt again to the issue of society 5.0, namely society and all social arrangements that are integrated with cyberspace. Educational management policies are needed to take advantage of advances in digital technology and educational computing in the era of the industrial revolution 4.0. Solutions that can be done include, among others, the suitability of the curriculum and learning process models provided as a provision of character education and optimal services to improve innovative and humanist constructive critical thinking skills and the readiness of facilities and infrastructure in digital-based learning.